The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1104/pp.111.4.1313
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Two Endo-1,4-β-Glucanase Genes in Pericarp and Locules of Wild-Type and Mutant Tomato Fruit

Abstract: The mRNA accumulation of two endo-l,4-P-o-glucanase genes, Cell and Cel2, was examined in the pericarp and locules throughout the development of normal tomato (Lycopersicon esculentum) fruit and the ripening-impaired mutants rin and Nr. Both Cell and Cel2 were expressed transiently at the earliest stages of fruit development during a period corresponding to cell division and early cell expansion. In the pericarp, the mRNA abundance of both genes increased markedly at the breaker stage; the leve1 of Cell mRNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Xyloglucan represents the predominant hemicellulose in many fruit including tomato, where degradation is apparent during ripening in wild-type fruit but not in fruit of the rin (ripening inhibitor) tomato mutant that soften extremely slowly (16). Fruit ripening has been associated with both endo-1,4-␤-glucanases (15,17) and xyloglucan endotransglycosylases (16,18); however, the importance of these and other as yet uncharacterized enzymes in modifying hemicellulose abundance, distribution, and interaction with other cell wall components in fruit has yet to be determined.…”
mentioning
confidence: 99%
“…Xyloglucan represents the predominant hemicellulose in many fruit including tomato, where degradation is apparent during ripening in wild-type fruit but not in fruit of the rin (ripening inhibitor) tomato mutant that soften extremely slowly (16). Fruit ripening has been associated with both endo-1,4-␤-glucanases (15,17) and xyloglucan endotransglycosylases (16,18); however, the importance of these and other as yet uncharacterized enzymes in modifying hemicellulose abundance, distribution, and interaction with other cell wall components in fruit has yet to be determined.…”
mentioning
confidence: 99%
“…Tomato flowers can also be induced to abscise even if they are pollinated when flowers are excised from the plant and exposed to ethylene (Valdovinos and Jensen, 1967). In tomato there is a family of EGase genes of at least six members, and the expression of two members of this family, Cell and Ce12, overlaps in ripening fruit and in flower abscission zones de1 Campillo and Bennett, 1996;Gonzalez-Bosch et al, 1996). Although both Cell and Ce12 mRNA are present in abscission zones and in ripening fruit, Cell mRNA is more abundant than Ce12 mRNA in abscission zones, whereas Ce12 mRNA is most abundant in ripening fruit.…”
mentioning
confidence: 99%
“…These results are in agreement with those of Amrani on grapes [10] and of Agravante and his collaborators [33] and Lohani and his collaborators [34] on the banana ripening. Furthermore, the study of gene expression encoding the parietal hydrolases showed that most of them are induced during ripening and regulated by ethylene [35][36][37][38]. These physiological processes allow embrittlement of the olives' cell walls, which has the consequence of facilitating the release of the phenolic compounds and the enrichment of the virgin olive oil by these compounds.…”
Section: Discussionmentioning
confidence: 99%